KUALITAS SARANA DAN PRASARANA SEBAGAI STRATEGI KEPALA SEKOLAH DALAM MENINGKATKAN MUTU PENDIDIKAN DI MIS RAUDLATUL MUNAWWARAH - Ali, Ismun (STIT AL MULTAZAM, 2023)
To improve the quality of education, not only competent educators are needed, but adequate and supportive facilities and infrastructure are needed, so that the learning atmosphere can run well according to the wishes of the parties in the school environment. Planning, procurement, inventory, use of facilities and infrastructure, maintenance, elimination and accountability. Research focuses on the quality of facilities and infrastructure as a strategy for school principals in improving the quality of education as an effort to advance schools. This research uses a qualitative method with interview models and field studies. From the results of the research that has been carried out, it can be concluded that the role of the Principal as an administrator in managing educational facilities and infrastructure at MIS Raudlatul Munawwarah and the strategy carried out includes procurement planning, inventory, use and elimination. It has been implemented and is running well, but it will be maximized if a library and sports field are built at MIS Raudlatul Munawwarah